Sustainability-Oriented Social Innovation Design: The Value of Co-Creation - Yan, Wu; Lei, Ren; Keye, Li (2019 IEEE Eurasia Conference on Biomedical Engineering, Healthcare and Sustainability (ECBIOS), 2019)
From the perspective of sustainability, this paper analyzes how stakeholders realize sustainable social innovation through co-creation. Through literature and case analysis, based on the group classification of social networks, this paper proposes three elements of social innovation: place creation, situation creation and relationship structure, and further sorts out the co-creation of meaning co-creation, behavior co-creation and value co-creation. The research shows that co-creation is a practical activity based on cultural identity, group interaction and resource integration, and stakeholders can achieve the goal of sustainable social innovation through meaning co-creation, behavior co-creation and value co-creation.
Keywords: Co-création; Communautaire; Coopération; Durabilité; Développement durable; Innovation sociale; Innovation sociale durable; Nouvelles technologies; Recherche; Réservé UdeM